FACE-TO-FACE LEARNING PROBLEMS AT STATE ISLAMIC UNIVERSITY DATOKARAMA PALU FOLLOWING THE COVID-19 PANDEMIC - Ramang; Retolia (Paedagogia: Jurnal Pendidikan, 2023)
Despite the fact that the COVID-19 pandemic has passed, the time during which it occurred is critical to discuss. It has impacted face-to-face learning problematic for students in the Islamic Religious Education Study Program. There are a number of studies that have been conducted to discuss the COVID-19 pandemic, both for the purposes of providing information to the community and in the field of education. However, research and writing related to the problems of post-COVID-19 face-to-face learning are still very limited. Through library studies and intensive field research from various literature and field facts, this study seeks to explain how the problems of face-to-face learning post-COVID-19 affect Islamic education courses and the Islamic religious education study program, FTIK UIN Datokarama Palu. The results of this study indicate that the problems of face-to-face learning after COVID-19 have appeared in the face-to-face learning process and have had an unfavorable influence on the behavior of entering lecture halls and students' reasoning power, both in the form of discussions and question and answer sessions, including in facing the Midterm Examination and end of semester exams. The conclusion is that problems in learning can be solved by lecturers using various learning strategies, both methods and strategies. This research still has limitations, namely only focusing on the Department of Islamic Religious Education, so it is still hoped that in the future there will be other studies that examine UIN Datokarama Palu in full.